Hydroclimatic Controls on the Isotopic (δ18 O, δ2 H, d-excess) Traits of Pan-Arctic Summer Rainfall Events - Mellat, Moein; Bailey, Hannah; Mustonen, Kaisa-Riikka; Marttila, Hannu; Klein, Eric S.; Gribanov, Konstantin; Bret-Harte, M. Syndonia; Chupakov, Artem V.; Divine, Dmitry V.; Else, Brent; Filippov, Ilya; Hyöky, Valtteri; et al. (Frontiers in Earth Science, 2021)
Arctic sea-ice loss is emblematic of an amplified Arctic water cycle and has critical feedback implications for global climate. Stable isotopes (δ18O, δ2H, d-excess) are valuable tracers for constraining water cycle and climate processes through space and time. Yet, the paucity of well-resolved Arctic isotope data preclude an empirically derived understanding of the hydrologic changes occurring today, in the deep (geologic) past, and in the future. To address this knowledge gap, the Pan-Arctic Precipitation Isotope Network (PAPIN) was established in 2018 to coordinate precipitation sampling at 19 stations across key tundra, subarctic, maritime, and continental climate zones. Here, we present a first assessment of rainfall samples collected in summer 2018 (n=281) and combine new isotope and meteorological data with sea ice observations, reanalysis data, and model simulations. Data collectively establish a summer Arctic Meteoric Water Line where δ2H = 7.6∙δ18O–1.8 (r2=0.96, p<0.01). Mean amount-weighted δ18O, δ2H, and d-excess values were -12.3 ‰, -93.5 ‰, and 4.9 ‰ respectively, with the lowest summer mean δ18O value observed in northwest Greenland (-19.9 ‰) and the highest in Iceland (-7.3 ‰). Southern Alaska recorded the lowest mean d-excess (-8.2 %) and northern Russia the highest (9.9 ‰). We identify a range of δ18O-temperature coefficients from 0.31 ‰/°C (Alaska) to 0.93 ‰/°C (Russia). The steepest regression slopes (>0.75 ‰/°C) were observed at continental sites, while statistically significant temperature relations were generally absent at coastal stations. Model outputs indicate that 68% of the summer precipitating air masses were transported into the Arctic from mid-latitudes and were characterized by relatively high δ18O values. Yet 32% of precipitation events, characterized by lower δ18O and high d-excess values, derived from northerly air masses transported from the Arctic Ocean and/or its marginal seas, highlighting key emergent oceanic moisture sources as sea ice cover declines. Resolving these processes across broader spatial-temporal scales is an ongoing research priority, and will be key to quantifying the past, present, and future feedbacks of an amplified Arctic water cycle on the global climate system.